Uncovering the Mitigating Psychological Response to Monitoring Technologies: Police Body Cameras Not Only Constrain but Also Depolarize - Patil, Shefali V.; Bernstein, Ethan S. (Organization Science, 2022)
Despite organizational psychologists’ long-standing caution against monitoring (citing its reduction in employee autonomy and thus effectiveness), many organizations continue to use it, often with no detriment to performance and with strong support, not protest, from employees. We argue that a critical step to resolving this anomaly is revisiting researchers’ fundamental assumptions about access to gathered data. Whereas previous research assumes that access resides nearly exclusively with supervisors and other evaluators, technological advances have enabled employee access. We hypothesize that with employee access, the psychological effects of monitoring may be far more complex than previously acknowledged. Whereas multiparty access may still decrease employee autonomy, it may also trigger an important psychological benefit: alleviating employees’ perceptions of polarization—the increasing social and ideological divergence between themselves and their evaluators. Access gives employees unprecedented opportunities to use the “objective” footage to show others their perspective, address evaluators’ erroneous assumptions and stereotypes, and otherwise defuse ideological tensions. Lower perceived polarization, in turn, attenuates the negative effects that low autonomy would otherwise have on employee effectiveness. We find support for these hypotheses across three field studies conducted in the law enforcement context, which has been a trailblazer in using technological advances to grant broad access to multiple parties, including employees. Overall, our studies shed light on the conflicting (and ultimately more innocuous) impact of monitoring and encourage scholars to break from prior approaches to account for its increasing egalitarianism.